ABCB1 Genetic Variants as Predictors of Irinotecan-Induced Severe Gastrointestinal Toxicity in Metastatic Colorectal Cancer Patients - Riera, Pau; Artigas-Baleri, Alícia; Salazar, Juliana; Sebio, Ana; Virgili, Anna C.; Arranz, María Jesús; Páez, David (Frontiers in Pharmacology, 2020)
Irinotecan is widely used in the treatment of metastatic colorectal cancer (mCRC) despite its severe toxicities. Toxicity is often associated with the UGT1A1*28/*28 genotype. An explanation for idiopathic toxicity beyond the UGT1A1 biomarker, however, remains a major concern for clinicians. One of the main irinotecan transporters is P-glycoprotein (P-gp), which is a hepatic efflux pump encoded by ABCB1. P-gp is involved in the biliary excretion of irinotecan and its active metabolite SN-38. We aimed to assess whether functional variants in ABCB1 also contribute to identifying patients at risk of toxicity. A cohort of 308 mCRC patients treated with irinotecan-based regimens were genotyped for polymorphisms in ABCB1 (rs1128503, rs2032582 and rs1045642). The effect of these variants and their haplotypes on irinotecan-induced severe toxicity (diarrhoea, neutropenia, asthenia, nausea and mucositis) was assessed. After adjusting for the relevant clinical and pathological parameters in the multivariate analysis, we found rs1128503 was significantly associated with severe diarrhoea and mucositis (P=0.014 and P=0.002, respectively). Additionally, rs2032582 was associated with severe mucositis (P<0.001). Our results show that rs1128503 genotyping could help to predict severe gastrointestinal toxicity induced by irinotecan.